Classics. The covering of skin defect after operative correction of the talipes equino-varus - Wiktor Dega (Chirurgia Narządów Ruchu i Ortopedia Polska, 2024)
After operative correction of adduction in the first stage of operative treatment (ligamentotomy, tendon elongation etc) of neglected congenital talipes equino-varus in children aged 4–6 years, some defect of the skin on medial side of the foot arises when correct position is assumed. The author covers this defect by pedicled skin graft from the dorsal surface of the foot, using the opportunity that on lateral surface of the inverted foot there is an excess of skin in the form round protuberance covering the cuboid bone and tuberosity of the fifth metatarsal. By flattening this round protuberance the area of the skin graft increases in such extent that not only the defect may be easily covered but the whole graft can be sutured to the edges of the operative wound.